2018
DOI: 10.3748/wjg.v24.i36.4119
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-sensing receptor in colorectal inflammation and cancer: Current insights and future perspectives

Abstract: The extracellular calcium-sensing receptor (CaSR) is best known for its action in the parathyroid gland and kidneys where it controls body calcium homeostasis. However, the CaSR has different roles in the gastrointestinal tract, where it is ubiquitously expressed. In the colon, the CaSR is involved in controlling multiple mechanisms, including fluid transport, inflammation, cell proliferation and differentiation. Although the expression pattern and functions of the CaSR in the colonic microenvironment are far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 130 publications
(126 reference statements)
0
32
0
Order By: Relevance
“…We detected a large cluster of chemokines co-expressed with several G-protein couple receptor signaling and cAMP signaling proteins, including GRM8 (a cell surface marker in CRC), GNG2/4/7, EDN2/3 and ADCY2/5/9 (adenylate cyclase). Two downregulated receptors LPAR1 (Lysophoatidic acid receptor), and CASR (Ca 2+ sensing receptor) involved in Ca 2+ homeostasis, were also detected within this cluster [40,41]. Taken together, these results lead us to speculate on a nexus between altered Ca 2+ signaling mediated by GPCRs, specifically chemokines, and their subsequent impact on the inflammatory signatures within distal tumors (LSCC).…”
Section: Suppressed Immune Signaling Predominates Left-sided Colon Tumentioning
confidence: 70%
“…We detected a large cluster of chemokines co-expressed with several G-protein couple receptor signaling and cAMP signaling proteins, including GRM8 (a cell surface marker in CRC), GNG2/4/7, EDN2/3 and ADCY2/5/9 (adenylate cyclase). Two downregulated receptors LPAR1 (Lysophoatidic acid receptor), and CASR (Ca 2+ sensing receptor) involved in Ca 2+ homeostasis, were also detected within this cluster [40,41]. Taken together, these results lead us to speculate on a nexus between altered Ca 2+ signaling mediated by GPCRs, specifically chemokines, and their subsequent impact on the inflammatory signatures within distal tumors (LSCC).…”
Section: Suppressed Immune Signaling Predominates Left-sided Colon Tumentioning
confidence: 70%
“…Together with this research, we summarized four points about CaSR functions and their corresponding mechanisms in tumors. (i) CaSR usually possesses different capabilities in various tumors and the mechanisms differ from each other; the function of CaSR is disease-specific (El Hiani et al, 2009;Joeckel et al, 2014;Aggarwal et al, 2015;Xie et al, 2017;Iamartino et al, 2018); (ii) in different tumors, CaSR may regulate the same downstream pathway in opposite ways to generate unlike actions (Aggarwal et al, 2015;Xie et al, 2017); (iii) CaSR may modulate different downstream pathways to induce the same or similar effects in different tumors (El Hiani et al, 2009;Joeckel et al, 2014;Xie et al, 2017); and (iv) CaSR may similarly regulate the same downstream pathway, but elicit diverse or even opposite results in different tumors (El Hiani et al, 2009;Casalà et al, 2013). Facing such conflicts, it is difficult to find a perfect theory to explain all these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in prostate, growing evidences indicate that the activation of CaSR may promote inflammation and eventually cancer development (Anract et al, 2019). In contrast, in the colon, the activation of CaSR is protective against inflammation and cancer (Iamartino et al, 2018). Consistently, in a clinical study with large sample sizes and long follow-up periods, Yang et al (2018) found that CaSR-positive expression status was essential for the antineoplastic effect of calcium in colorectal cancer (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
“…This lower expression seems a consequence of epigenetic alterations since a huge number of CpG islands of the CasR gene are highly methylated in colorectal tumors. Moreover, the presence of some miRNAs, such as miR-21, miR-135a, miR-135b, miR-145, miR-146b, and miR-503, reduced the expression of CasR in colorectal tumors [105]. The relevance of CasR in colorectal tumorigenesis was demonstrated in the conditional knock-out of CasR in intestinal epithelium which presented intestinal hyperproliferation, developed pre-malignant lesions and were more susceptible to azoxymethane.…”
Section: Calcium-sensing Receptor (Casr)mentioning
confidence: 99%